IMPROVING THE STUDENTS’ READING COMPREHENSION USING TIERED TASKS STRATEGY - Ratu Yulianti Natsir; Asrawiah Asrawiah (Universitas Muhammadiyah Makassar, 2013)
This research aimed to explain the students’ achievement in literal reading comprehension using Tiered Tasks Strategy, as well as to explain the students’ achievement in interpretative reading comprehension using Tiered Tasks Strategy. This research used Classroom Action Research and applied to cycles in the application, they are cycle 1 and 2 with 4 meetings in every cycle. The improvement of students’ ability to write narrative text using Tiered Tasks Strategy had an effective effect. The researcher found that before the application of tiered tasks strategy the students’ score is 52.53(fair) but after using the method the students’ score in cycle I is 62.14 and in the cycle, II become 77.18. So, the improvement of the students’ score of d-test to cycle I is 18.93% whereas the development of the students’ ability of d-test to cycle II is 47.80% and the improvement from cycle I to cycle II is 24.22%.Keywords: Reading, Tiered, Strategy